Resolving Visible Emission Lines in Hydrogen Diffusion Flames - Muyi Pan; Xuanqi Liu; Yufeng Lai; Yuchen Zhang; Yang Zhang (Aerospace)
The hydrogen diffusion flame is commonly described as difficult to see in the visible range. However, even in controlled laboratory conditions with careful imaging, the flame appears reddish. Previous research has reported a variety of colours generated from hydrogen flames. Some researchers believe that the visible colour is due to sodium in airborne dust. Other studies suggest the flame colour is caused by the vibration–rotation band of water vapour. In addition, <semantics>H−α</semantics> emits radiance in the visible range; therefore, the visible colour of the hydrogen flame could be contributed from the <semantics>H−α</semantics> emission. Nevertheless, a definitive conclusion to explain the visible reddish colour of the hydrogen flame is lacking. This paper reports precisely instrumented spectroscopic imaging tests, calibration, and data processing in order to resolve the spectral lines in the red colour zone (580–700 nm). This study used a spectrograph and a DSLR camera to capture the spectrum of hydrogen diffusion flames under different co-flow conditions. The values of emission lines in this range were compared with the databases provided by HITRAN molecular spectroscopy and the National Institute of Standards and Technology (NIST). The results of this study show that <semantics>H−α</semantics> emission is highly likely to appear in a hydrogen diffusion flame, which contradicts the previous hypothesis. This work may provide new insight into hydrogen-based combustion.